Romney Vs. Obama : Election 2012 - Benoit, Peter (New York : Children's Press, 2013)
"Read about the lives and political positions of this year's Democratic and Republican presidential candidates, and learn how one of these men will shape the nation's future." -- P. [4] of cover.
Keywords: American history -- Non-fiction